1982
DOI: 10.1002/1097-4679(198207)38:3<486::aid-jclp2270380304>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Defense mechanisms in reactive and process schizophrenics

Abstract: Divided schizophrenics into reactive and process groups (20 males and 20 females in each group) on the basis of three criteria: Premorbid adjustment, role orientation, and paranoid‐nonparanoid status. All were administered the Defense Mechanism Inventory, which measures five clusters of defenses. Reactives had significantly higher scores than process patients on Turning against Self and Projection. Process patients had significantly higher scores on Reversal. No significant differences between groups were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Schueler, Herron, Poland, and Schultz (1982) rated 80 schizophrenic inpatients for their manifestation of avoidance of others, turning against the object, projection, and turning against the self, and compared these ratings with DMI scores.…”
Section: Concurrent Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Schueler, Herron, Poland, and Schultz (1982) rated 80 schizophrenic inpatients for their manifestation of avoidance of others, turning against the object, projection, and turning against the self, and compared these ratings with DMI scores.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…For males only, T AS and REV were higher than in a nonpatient sample while TAO and PRO were lower. Within a sample of schizophrenics, Schueler et al (1982) found that patients diagnosed as reactive schizophrenic scored 126 6. Approaches to Measuring Defenses higher on PRO and T AS than did those diagnosed as process schizophrenic, who in turn scored extremely high on REV (mean = 50+).…”
Section: Psychiatric Patientsmentioning
confidence: 99%
“…Using this measure, Rubino et al (1991) found that psychotic subjects and subjects with schizophrenia used qualitatively different defences when compared with normal controls and other diagnostic groups. Other projective measures employed include the Frankfurt Complaint Questionnaire (Bulnes, Valdés, Aragón, & López Fernández, 1997), the Utrecht Coping List (Van den Bosch & Rombouts, 1997), the Defense Mechanism Inventory (DMI; D' Angelo & Wolowitz, 1986;Schueler, Herron, Poland, & Schultz, 1982), the Picture Interpretation Task (Kaufman, 1973) and interpretation of artwork of subjects with schizophrenia (Anstadt & Krause, 1989). However, there has been little consensus based on the results of these studies.…”
Section: Introductionmentioning
confidence: 99%